2011
DOI: 10.1098/rsbl.2011.0756
|View full text |Cite
|
Sign up to set email alerts
|

Pre-fledgling oxidative damage predicts recruitment in a long-lived bird

Abstract: Empirical evidence has shown that stressful conditions experienced during development may exert long-term negative effects on life-history traits. Although it has been suggested that oxidative stress has long-term effects, little is known about delayed consequences of oxidative stress experienced early in life in fitness-related traits. Here, we tested whether oxidative stress during development has long-term effects on a life-history trait directly related to fitness in three colonies of European shags Phalac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 23 publications
5
72
2
Order By: Relevance
“…Overall, our results may suggest that variation in the levels of serum LP of offspring has a genetic basis and might be further influenced by environmental conditions, including maternal effects, that the chicks experience during development. Offspring variation in the capacity to deal with oxidative stress can have important fitness consequences through increased survival (Bize et al, 2008;Noguera et al, 2012) Costantini and Dell'Omo, 2015). Furthermore, in our study, male gular color and LP during courtship were positively related; if covariation between offspring and father LP levels have a positive impact on female fitness (through increased survival or reproduction of offspring), the evolution of sexual traits that indicate the ability to deal with oxidative stress, such as the gular color of male brown boobies, may be favored (von Schantz et al, 1999).…”
Section: Sources Of Individual Variation In Chick Oxidative Stressmentioning
confidence: 99%
“…Overall, our results may suggest that variation in the levels of serum LP of offspring has a genetic basis and might be further influenced by environmental conditions, including maternal effects, that the chicks experience during development. Offspring variation in the capacity to deal with oxidative stress can have important fitness consequences through increased survival (Bize et al, 2008;Noguera et al, 2012) Costantini and Dell'Omo, 2015). Furthermore, in our study, male gular color and LP during courtship were positively related; if covariation between offspring and father LP levels have a positive impact on female fitness (through increased survival or reproduction of offspring), the evolution of sexual traits that indicate the ability to deal with oxidative stress, such as the gular color of male brown boobies, may be favored (von Schantz et al, 1999).…”
Section: Sources Of Individual Variation In Chick Oxidative Stressmentioning
confidence: 99%
“…In birds, prenatal elevation of corticosterone levels is associated with postnatal oxidative costs (40), agreeing with our result of the longterm effect of early exposure to corticosterone on oxidative damage. Importantly, high levels of oxidative damage at fledging are related to a reduction in adult survival in seabirds (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…The opposite effects of these two important environmental factors (food availability (this study) vs. parasitism (De Coster et al 2012)) on the oxidative status of male and female nestlings highlights the different sensitivities of the two sexes to environmental factors, with subsequent consequences on physiological mediators of variation in fitness (Noguera et al 2012;Losdat et al 2013). The higher sensitivity of female nestlings to food limitation early in life suggests that females might pay a higher price for the increasing mismatch between food availability and demand due to climate change observed in many bird species (Thomas et al 2001;Visser et al 2003) Generally, we found no strong relationships between the measured markers of oxidative damage or protection and nestling growth, fledging size or mass.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant capacity is positively, while oxidative damage negatively related to survival (Freeman-Gallant et al 2011;Saino et al 2011). Furthermore recent studies showed that the ability of nestlings to cope with oxidative stress predicts their fledging success (Losdat et al 2013) and their recruitment probability (Noguera et al 2012), highlighting that an efficient antioxidant protection is beneficial from the first stages of life. However, investment in such an efficient oxidative protection is likely associated with costs.…”
Section: Introductionmentioning
confidence: 99%